Critical feminist social work analysis of sexual violence perpetrator profiles: a hermeneutic phenomenological study in garut regency - Nahar Nahar; Bambang Rustanto; Tuti Kartika; Susilawati Susilawati; Ellya Susilowati; Aryohaji Istyawan (Indonesian Counselor Association (IKI), 2026)
This study deconstructs the profile of sexual violence perpetrators in Garut Regency, Indonesia, through a critical feminist social work analysis using a hermeneutic phenomenological approach. Data were obtained from in-depth interviews with nine participants at the Integrated Service Unit for the Protection of Women and Children (UPTD-PPA), comprising three survivors and six service providers. Findings show that perpetrators are predominantly individuals within survivors' closest relational circles, rather than unfamiliar strangers, operating through grooming and sustained by cognitive distortions that normalize victim-blaming. Drawing on critical feminist theory, feminist social work practice, and hegemonic masculinity, perpetration is understood as an assertion of unequal power rather than uncontrollable sexual impulse. The ecological perspective further reveals how family and community systems fail to sustain protective functions, allowing patriarchal structures to perpetuate impunity. This study recommends a shift in social work intervention toward emancipatory structural advocacy